2010
DOI: 10.1088/0022-3727/43/31/315501
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and viscosity of Al2O3 nanofluid based on car engine coolant

Abstract: Various suspensions containing Al2O3 nanoparticles (<50 nm) in a car engine coolant have been prepared using oleic acid as the surfactant and are tested to be stable for more than 80 days. Thermal conductivity and viscosity of the nanofluids have been investigated both as a function of concentration of Al2O3 nanoparticles as well as temperature between 10 and 80 °C. The prepared nanofluid, containing only 0.035 volume fraction of Al2O3 nanoparticles, displays a fairly higher thermal conductivity than the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(61 citation statements)
references
References 43 publications
(80 reference statements)
4
54
0
1
Order By: Relevance
“…The first one is based on the physical or chemical treatment of the nanoparticles, in particular for carbon nanotubes [28] and the use of dispersing agents such as polymers. The dispersing of nanoparticles can also be obtained from mechanical methods such as sonication [2,4,17,21], ultrasonication [3,[5][6][7]12], homogenization [6,12] and high stirring [3,5,14]. The dispersion and the stability of the nanofluids are mainly obtained by gathering some of the previous mentioned methods.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is based on the physical or chemical treatment of the nanoparticles, in particular for carbon nanotubes [28] and the use of dispersing agents such as polymers. The dispersing of nanoparticles can also be obtained from mechanical methods such as sonication [2,4,17,21], ultrasonication [3,[5][6][7]12], homogenization [6,12] and high stirring [3,5,14]. The dispersion and the stability of the nanofluids are mainly obtained by gathering some of the previous mentioned methods.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that viscosity decreases exponentially with the increase of temperature. Kole et al [18] investigated Al 2 O 3 -car engine coolant nanofluid and found that the Brownian motion of the nanoparticles in the fluid plays an important role in understanding the viscosity of nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1, one can see their results on an enhancement of radiator thermal effectiveness versus flow rate during nanofluids with different volume concentrations implementation. An experimental study on nanofluids viscosity in car radiator was carried out by Kole and Dey (2010). They used alumina nanoparticles dispersed in water and stabilized by oleic acid.…”
Section: Fig 1 Automotive Cooling System Componentsmentioning
confidence: 99%